Study the effect of some herbs used in diet on germination, growth, mitotic division and total nucleic acids content of Triticum aestivum L. plant - Eliwa, Amal Mohamed (Al-Mukhtar Journal of Sciences, 2009)
The present investigation was carried out to study the effect of three wild plants (Cichorium intybus, Cassia angustifolia and Foeniculum vulgare) which are used as spices in the Libyan food on the germination, growth and nucleic acids content of wheat plant. The results obtained revealed a great reduction in germination percentage, root length, shoot length, fresh weight, dry weigh, mitotic index , nucleic acids content in the treated plants when compared with the corresponding control and also the appearance of many types of mitotic aberrations via the depression of spindle fibers or disturbance in the formation and function of chromosomal movement-mechanism at metaphase and ana-telophase, liquefaction of DNA and/or increasing its polymerization leading to chromosomal stickiness. The later results can be explained due to the toxic effect of the glycosidic substances, alkaloides and the volatile oils found in the plants under study.